High-Temperature Hydrothermal Fe-Ti Oxide Mineralization in The Arızlı Ophiolitic Mélange, Western Anatolia - CİHAN YALÇIN; Adil Ozdemir (Geological Agency, 2026)
The Arızlı Ophiolitic Complex in western Anatolia provides a distinctive geological context for comprehending Fe-Ti oxide mineralization processes in ophiolitic settings. This research examines the geochemical and mineralogical properties of Fe-Ti oxides using extensive fieldwork and laboratory investigations, including X-ray fluorescence spectrometry (XRF), inductively coupled plasma mass spectrometry (ICP-MS), and X-ray diffraction (XRD). Ten samples were obtained from ultramafic and mafic rocks, displaying notable mineralization characteristics. The geochemical investigations indicated Fe₂O₃ concentrations between 10.52 % and 19.93 %, with TiO₂ contents ranging from 2.17 % to 13.63 %, suggesting hydrothermal and metasomatic processes. Discriminant diagrams, including Si-Al, Fe/Ti-Al/(Al+Fe+Mn), and Fe-Six2-Mn, validated the hydrothermal genesis of the deposit, supplemented by volcano-sedimentary processes Elevated Fe/Ti ratios and the clustering of samples within high-temperature hydrothermal domains ( 300-500° C) suggest that hydrothermal fluids and metasomatic overprinting played a significant role in the formation of Fe-Ti oxide mineralization. A comparative analysis with other ophiolitic complexes, such as the Oman and Pindos ophiolites, underscores both common mineralogical-geochemical traits and unique attributes of Tthe Arızlı Ccomplex, notably its comparatively elevated aluminium enrichment. This work examines critical deficiencies in comprehending the genetic regulations and structural impacts on Fe-Ti oxide mineralization in ophiolitic environments. The findings offer a valuable foundation for subsequent research and resource evaluations, enhancing regional metallogenic models of hydrothermal Fe-Ti mineralization in ophiolitic environments.